High-Frequency QPOs as a Product of Inner Disk Dynamics around Neutron Stars - Erkut, M. Hakan (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 USA, 2011)
The kHz QPOs observed in a neutron star low mass X-ray binary are likely to be produced in the innermost regions of accretion disk around the neutron star. The rotational dynamics of the inner disk can be characterized by the presence of either sub-Keplerian or super-Keplerian accretion flow depending on the relative fastness of the neutron spin as compared to the Keplerian frequency at the inner disk radius. Within the magnetosphere-disk interaction model, the frequency difference between the two kHz QPOs observed in a given source can be estimated to be slightly higher than or nearly around the neutron star spin frequency if the neutron star is a slow rotator and less than the stellar spin frequency if the neutron star is a fast rotator.
Keywords: Accretion and accretion disks; Oscillations; Neutron stars; X-ray binaries; Oscillations